IMAM KAMPUANG SEBAGAI WALI HAKIM: Analisis Terhadap Putusan Pengadilan Agama Talu Nomor 502/Pdt.G/2011/PA Tentang Itsbat Nikah - Alim, Abdul; Rosman, Edi (Alhurriyah, 2018)
Marriage is a facility that Allah arranges in such a way that human biological needs are channeled and fulfilled respectfully and well. To carry out a marriage, the role of the guardian of marriage is very important because in his hand a marriage becomes legitimate, in addition to fulfilling the other pillars, including witnesses and dowry. If these pillars are not fulfilled and ignored, the marriages that are carried out are not recognized by the syarak. The decision of the Talu Religious Court by ordering a marriage without a legal guardian according to the rules of Islamic law and legislation in Indonesia certainly seems to have ignored the provisions of the fiqh and the positive law that applies in Indonesia. This is because there are no rules in fiqh and also positive laws that allow a priest to be allowed to marry someone who has no relationship with him. The appointment of the village priest as the guardian of the judge in a marriage is not based on reasons that can be justified by syarak, because in the subsection of the judge's guardian in the constellation of Islamic law and the positive law applicable in Indonesia is the government or the person authorized by the government to be the judge's guardian. In the marriage certificate request that has been granted by the panel of judges, the Religious Religious Court Number: 502 / Pdt.G / 2011 / PA has ignored important aspects in a legal product because of lack of attention to aspects of Islamic law (fiqh) that never provide opportunities to people who are not have a relationship with a woman nasab.